2022
DOI: 10.3390/su14084766
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: New Prevention and Protection Measures

Abstract: As of the end of February 2021, more than 420,000,000 confirmed cases of COVID-19 have been reported worldwide, with 5,856,224 deaths. Transmission of the different genetically engineered variants of SARS-CoV-2, which have been isolated since the beginning of the pandemic, occurs from one infected person to another by the same means: the airborne route, indirect contact, and occasionally the fecal–oral route. Infection is asymptomatic or may present with flulike symptoms such as fever, cough, and mild to moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Law n.24 is still being implemented, and several years are needed to assess the effects on patient safety culture and litigation prevention to achieve the stated goals by monitoring adverse events and reducing medical liability and the costs of the healthcare system [ 29 , 30 ]. Several studies suggested that educational programs and patient safety culture improvement lead to a reduction in the number of adverse events and greater patient and HCW safety perspectives in healthcare facilities [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Law n.24 is still being implemented, and several years are needed to assess the effects on patient safety culture and litigation prevention to achieve the stated goals by monitoring adverse events and reducing medical liability and the costs of the healthcare system [ 29 , 30 ]. Several studies suggested that educational programs and patient safety culture improvement lead to a reduction in the number of adverse events and greater patient and HCW safety perspectives in healthcare facilities [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hand hygiene, social distancing, and quarantine are essential to combat the virus [ 3 ]. Also, the use of personal protective equipment, including face protecting masks, has ensured greater control of the spread of the virus [ 4 ]. Furthermore, the large-scale use of vaccines has favorably changed the initial scenario of the pandemic by reducing contagions and drastically decreasing the hospitalization of people infected with the virus.…”
Section: Introductionmentioning
confidence: 99%
“…High-risk workplaces like RCFs require design and implementation of multifaceted IPAC interventions that extend beyond PPE, quarantine and isolation to also ensuring high vaccination rates and optimizing physical infrastructure e.g. implementing adequate air handling systems and ventilation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%